2023
DOI: 10.3390/su15021456
|View full text |Cite
|
Sign up to set email alerts
|

Keep Playing or Restart? Questions about the Evaluation of Video Game Addiction from a Systematic Review in the Context of COVID-19

Abstract: This is a systematic review of the impact of COVID-19 confinement on problematic video game use and addiction. The research questions were: (1) What instruments were used to measure problematic gaming and video game addiction in the context of COVID-19; (2) how many studies made comparisons with analogous samples measured at two timepoints (pre-confinement and confinement); and (3) what were the results of these studies in terms of a possible increase of problematic gaming and video game addiction during confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Li et al, 2023). The theory of Ternary Interaction provides a framework for understanding the interplay between the environment, individual and behavior and also highlights the significance of environmental stimuli in shaping behavior (Oceja, Villanueva-Blasco, Vázquez-Martínez, Villanueva-Silvestre, & Al-Halabí, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2023). The theory of Ternary Interaction provides a framework for understanding the interplay between the environment, individual and behavior and also highlights the significance of environmental stimuli in shaping behavior (Oceja, Villanueva-Blasco, Vázquez-Martínez, Villanueva-Silvestre, & Al-Halabí, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors also pointed out that the differences in methods adopted to collect data likely influenced such results. Lastly, in their systematic review, Oceja et al [23] found a small number of studies on PG during COVID-19, which led to conflicting and inconclusive results due to the heterogeneity of methods.…”
Section: Objectives Of the Present Systematic Review And Meta-analysismentioning
confidence: 99%